Chinese women with melasma exhibit a low minimal erythema dose to both UVA and UVB. Issue 1 (28th July 2021) - Wang, Zixu; Lu, Fengyan; Li, Xing; Guo, Yanni; Li, Jiajing; He, Li
Abstract: Background: Melasma is a common disorder manifested by symmetric hyperpigmentation of sun‐exposed skin. Although ultraviolet (UV) radiation is a known risk factor of melasma, whether skin sensitivities to UVA and/or UVB differ between healthy controls and female patients with melasma is unknown. Methods: Minimal erythema dose (MED)‐UVA and MED‐UVB results were compared between female patients with melasma and healthy controls. Additionally, relationships between MED values and Melasma Area and Severity Index (MASI) scores, and skin color were assessed. Results: The melasma and control groups included 142 and 137 subjects, respectively. Compared with healthy control group, our melasma group had lower MED‐UVA ( P < .001) and MED‐UVB ( P < .05). MASI scores were negatively correlated with MED‐UVA and MED‐UVB ( P < .001). Additionally, Skin a* values in melasma‐involved skin were negatively correlated with MED‐UVA ( P < .05). Skin b* values in melasma‐involved skin were negatively correlated with MED‐UVB and MED‐UVA ( P < .05). Conclusions: Patients with melasma exhibit a low MED to both UVA and UVB, rendering them have a predisposition to an increased UV sensitivity. Because of the association between melasma and UV sensitivity, sun exposure should be avoided to alleviate or prevent melasma.